Islam : an introduction - Raudvere, Catharina (2015)
Assesses Islam as a global phenomenon, examining history and universal values, social and ritual practices, in both Islamic countries and diaspora communities
The Muslim world : past and present -- The early history of Islam and Muhammad as a historical person -- The canonical texts of Islam : historical documents and personal piety -- Sharia : the law of Allah and human free will -- The festivals of the Muslim year and lifecycle rituals : community and celebration -- Between canonical obligations and devotional practices : everyday religiosity -- Shiʻi Islam : religious authority and remembered martyrdom -- Muslim ethics : ideals, responsibilities and the challenges of modern life -- Political Islam : visions and nightmares
Includes bibliographical references and index
Keywords: Islam